Utilizing Memes for Vocabulary Learning Development: EFL Senior High School Students’ Viewpoints - Amanda, Callista; Hadiyanti, Widi (Balai Bahasa Sumatra Barat, 2024)
The current era, the advancement of technology, digital media, and its contents have become more relevant in teaching and learning activities. One that is close to EFL students and applicable to overcome their problems dealing with vocabulary development is memes. This research aims to investigate the effectiveness of using memes, the ways this activity helps the 26 twelfth graders learn vocabulary with the reasons behind it. This research employed mixed methods. Vocabulary pre and post-tests were exploited to find out the effectiveness of utilizing memes for the students’ learning. A questionnaire consisting of eleven statements and five open-ended questions was employed to detect the students’ thoughts about the aspects stated and further explanation on how memes influence their vocabulary learning. Using ttests and descriptive analyses, it was found that exploiting memes can effectively improve students’ EFL vocabulary learning, with the mentioned aspects and reasons revealed in their responses to the questionnaire. AbstrakPada era sekarang, kemajuan teknologi, media digital, beserta konten-kontennya semakin relevan dalam kegiatan belajar mengajar. Salah satu yang dekat dengan siswa pembelajar bahasa inggris dan dapat diterapkan untuk mengatasi permasalahan dalam pengembangan kosa kata bahasa inggris mereka adalah meme. Penelitian ini bertujuan untuk menyelidiki efektivitas penggunaan meme, serta bagaimana kegiatan ini membantu 26 siswa kelas dua belas mempelajari kosakata bahasa inggris beserta alasan di baliknya. Penelitian ini menggunakan odel mix methode. Tes kosakata sebelum dan sesudah pelaksanaan pembelajaran dipakai untuk mengetahui efektivitas penggunaan meme dalam pembelajaran siswa. Sebuah kuesioner yang terdiri dari sebelas pernyataan dan lima pertanyaan terbuka digunakan untuk mengetahui pemikiran siswa mengenai aspek-aspek yang disebutkan serta penjelasan lebih lanjut tentang bagaimana meme mempengaruhi pembelajaran kosakata mereka. Menggunakan analisis uji-t juga analisis deskriptif, ditemukan bahwa eksploitasi meme dapat secara efektif meningkatkan pembelajaran kosakata bahasa inggris siswa, disertai dengan aspek beserta alasannya terungkap dalam tanggapan mereka terhadap kuesioner